Islet cilia and glucose homeostasis - Melena, Isabella; Hughes, Jing W. (Frontiers in Cell and Developmental Biology, 2022)
Diabetes is a growing pandemic affecting over ten percent of the U.S. population. Individuals with all types of diabetes exhibit glucose dysregulation due to altered function and coordination of pancreatic islets. Within the critical intercellular space in pancreatic islets, the primary cilium emerges as an important physical structure mediating cell-cell crosstalk and signal transduction. Many events leading to hormone secretion, including GPCR and second-messenger signaling, are spatiotemporally regulated at the level of the cilium. In this review, we summarize current knowledge of cilia action in islet hormone regulation and glucose homeostasis, focusing on newly implicated ciliary pathways that regulate insulin exocytosis and intercellular communication. We present evidence of key signaling proteins on islet cilia and discuss ways in which cilia might functionally connect islet endocrine cells with the non-endocrine compartments. These discussions aim to stimulate conversations regarding the extent of cilia-controlled glucose homeostasis in health and in metabolic diseases.